FEASIBILITY OF STUDENTS WORKSHEETS USING CONCEPTUAL CHANGE TO REMIDIATE MISCONCEPTIONS ON CHEMICAL BONDING MATERIAL - Fitrah Nadia Rizqiyyah; Dian Novita (JCER (Journal of Chemistry Education Research), 2022)
This research aims to determine the feasibility of student worksheetss to remediate misconceptions on chemical bonding material, sub-material ionic bonding and covalent bonding with the development of conceptual change models on student worksheets. The research method used is research and development (R&D). Three tier diagnostic tests are used to determine misconceptions experienced by students. Quantitative data analysis is used to determine the classification of students' conceptions and also the remission of misconceptions. The results of this study obtained the feasibility of a student worksheets which was assessed from validity, practicality, and effectiveness. Validity gets a percentage of 83.01% with a very valid category. Practicality gets a percentage of 93.54% with a very practical category. Effectiveness in terms of the N-Gain score in the high and medium level category. This shows that the  student worksheets which developed can classified as feasible, so it can be used to remediate students misconceptions on chemical bonding material  Keywords: Feasibilty, Student Worksheets, Conceptual Change, Misconception